Analisis Pelaksanaan Batas Maksimum Pemberian Kredit (BMPK) dan Implikasinya terhadap Kesehatan Bank: Tinjauan Literatur - Esra Sparia Sihaloho; Rahel Rut Syeba Rajagukguk; Ester Novianti Sinaga; Angel Febriyanti Sinaga; Hamonangan Siallagan; Christnova Hasugian (Mathematics Education Study Program, 2025)
This study aims to analyze the implementation of the Legal Lending Limit (LLL) in the banking sector and its implications for bank health. Legal Lending Limit (LLL) is a regulation set by Bank Indonesia and the Financial Services Authority to control concentration risk in lending, which aims to maintain financial system stability and public confidence in banks. Through the literature study method, this research identifies various challenges in the implementation of Legal Lending Limit (LLL), including the impact of economic fluctuations and the need for wider access to financing. The results show that while Legal Lending Limit (LLL) serves as a risk control tool, its implementation requires a deep understanding from banks and financial institutions to achieve a balance between risk control and credit provision. The study recommends improved education and training for relevant parties as well as the development of more responsive policies from banking authorities. The findings are expected to provide insights for the development of healthier and more sustainable banking practices.